The Problems of Renewable Power Plant Construction Affecting the Energy Security of Thailand - Songkrit Trerutpicharn; Waranon Kongsong; Kijbodi Kongbenjapuch; Seree Tuprakay; Boonchuay Srithammasak; Sumate Roykulcharoen (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
The objectives of this research were to study the process of submitting an application for every license that affects the success of renewable power plant construction and the energy security of Thailand in accordance with the Energy Industry Act 2007, the engineering factors used in the selection of all types of renewable power plant construction, and the Key Performance Indicators of all types of renewable power plant construction. The data analysis was divided into two sections. For the first section, the quantitative data was collected from the questionnaire conducted by the purposive sampling that included those related to renewable power plant projects, which asked the questions about the rules and regulations and power purchase agreement under the Energy Industry Act 2007. As for the factors influencing the project success, the private sector, combined in the sample group, included the design engineers, consulting and control engineers, and contractors. The 400 engineers were randomly selected from the registration of the Council of Engineers, including senior professional engineers, professional engineers, associate engineers, and adjunct engineers. In the second section, the qualitative data came from the in-depth interviews with five specialists and experts in the renewable power plant industry and in legal knowledge about the rules and regulations and power purchase agreements according to the Energy Industry Act 2007, who work in the Metropolitan Electricity Authority, a renewable power plant construction company, a renewable energy consulting company, in the field of renewable power plant investment, and as a renewable power plant specialist (Office of the Energy Regulatory Commission). The data was analyzed by using the following statistics: percentage, frequency, mean, standard deviation, and the Enter method of multiple regression. According to the results, the overall success of using the engineering factors in selecting a renewable power plant establishment has the mean at a high level. With regard to the types of power plants, the solar power plant is ranked at the top, followed by the second, the biomass power plant; then, the waste-to-energy power plant, the biogas power plant, and the wind power plant, respectively. The type of power plant with a moderately high mean is the hydroelectric power plant. The findings show the engineering factors related to the success of all types of renewable power plants. Moreover, regarding the problem of energy policy, deciding which type of energy to use is highly complicated because there are many dimensional reasons and no form of energy is the best or the worst option. However, it is not too difficult for specialists to make a decision.